HOW 'BLUE' DO MARINE AND FISHERIES COMPANIES SUPPORTING SDG 14? - Fadillah, Haqi; Yudi (Media Riset Akuntansi, Auditing & Informasi, 2025)
The aim of this study is to identify whether the aquaculture and wild fisheries sector entities in Indonesia have fully disclosed the blue economy report. The utilisation of descriptive analysis and content analysis is employed to quantify the extent of blue economy disclosure in annual reports. The technique used is the scoring technique from the indicators of Law No. 32 of 2014 regarding Maritime which was last amended into Law Number 11 of 2020 regarding Job Creation in the Maritime and Fisheries Sector and GRI 13: Agriculture, Aquaculture and Wild Fisheries. The study result shows that the average disclosure is only in narrative and numerical form. Entities have not presented it using tables, graphs, or trends. The disclosure score, which is still very minimal, indicates that these companies have not based their sustainability report preparation on Law Number 11 of 2020 and GRI 13.